Analisis Rencana Pelaksanaan Pembelajaran (RPP) Tematik Muatan IPA Ditinjau Dari Kompetensi Abad 21 dan Higher Order Thinking Skills (HOTS) - Mardiana, Mardiana (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to analyze the lesson plans developed by elementary school teachers related to 1) 21st-century skills-based learning strategies, 2) learning media using ICT and natural objects, 3) HOTS-based learning evaluation. This research uses the descriptive qualitative method. The research instrument was in the form of a lesson plan analysis sheet. Data on each aspect of the lesson plans were calculated for validation. The results of this study are 1) The learning strategy shows very valid and high criteria; 2) The selection of learning media shows very valid and moderate criteria; 3) Learning evaluation shows very valid and moderate criteria. This study concludes that the lesson plans used by teachers are not all HOTS-based.